THE INFLUENCE SHAKESPEAREAN DRAMAS ON DRAMATURGY - Sobirjonova, J.; Usmonova, S. (Educational Research in Universal Sciences, 2023)
Most people agree that William Shakespeare’s plays have had the greatest impact on English-language theater. Shakespeare’s plays are still performed and modified for new audiences and cultures despite the fact that he penned them in the late 16th and early 17th centuries. According to Guinness World Records, Shakespeare remains the world’s best-selling playwright, with sales of his plays and poetry believed to have achieved in excess of four billion copies in the almost 400 years since his death. He is also the third most translated author in history Shakespeare frequently examined parent-child conflict.[1] Shakespeare’s dramatic works have had a significant influence on dramaturgy—the craft of creating and staging plays on the stage—which is one of the factors contributing to their enduring appeal. [1] “William Shakespeare. Ten startling Great Bard- themed world records” Genius World records. 23April 2014.